Assessment of Serum Lipid Profile in Patients with Hypertension (Academia Journal of Medicine, 2021)
Background: Hypertension had a global burden on 26.4% of the adult population in 2000, and projections reveal a rise to 29.2 per cent by 2025. Given its high prevalence and associated risks of progression to cardio-vascular disease (CVD) and stroke, early diagnosis becomes crucial. The present study was undertaken for assessing serum lipid profile in patients with hypertensive patients. Subjects and Methods: A total of 50 patients with confirmed diagnosis of essential hypertension were enrolled. Another set of 50 age and gender matched subjects were taken as healthy controls. Complete demographic and clinical details of all the subjects were obtained. Blood samples were obtained from all the subjects and were sent to laboratory where autoanalyzer were used for assessment of serum lipid profile. All the results were recorded in Microsoft excel sheet and were analyzed by SPSS software. Results: Mean Triglycerides among the patients of the essential hypertension group and control group was 1.36 and 1.15 respectively (p- value < 0.05). Mean total cholesterol levels among the patients of the essential hypertension group and control group was 4.96 and 4.05 respectively (p- value < 0.05). Conclusion: Serum lipid profile is significantly deranged in essential hypertension patients.
Keywords: Essential hypertension; Lipid profile